Less invasive stabilization system (LISS) in the treatment of distal femoral fractures - Schütz, M; Müller, M; Kääb, M; Haas, N (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2003)
The treatment of distal femoral fractures has been associated with a high rate of complications for a long time. Although implants and surgical techniques have improved, plate osteosynthesis and intramedullary nailing have been accompanied by a high occurrence of infection, non-union and malalignment. The treatment of soft tissue envelopes using "biological" osteosynthesis and minimally invasive approaches has resulted in a decrease in complication rates and ultimately led to the concept of the less invasive stabilization system (LISS). This is an extramedullary-applied, internal fixator shaped according to the implantation site anatomy, with minimal invasiveness. The purpose of this study was to present this new surgical technique and draw attention to its advantages and importance. Although this is not a scientific paper, we hope to provide enough evidence of the LISS usefulness. The main LISS components include multiple-fixed angle screws and an insertion handle for submuscular sliding of a fixator and placement of percutaneous, self-drilling, unicortical screws for fixation of the diaphyseal fracture fragments. The LISS has been designed to preserve periosteal perfusion and to facilitate a minimally invasive application. Since the first implantation of the LISS, only a few studies have been published on its use in treatment of distal femoral fractures. The rate of infection has been low, ranging from 0 to 4%. The rate of delayed union has been between 2.4 and 6.1%, but delayed unions do not necessarily lead to secondary bone grafting or repeat osteosynthesis as the LISS has a high and lasting stability. When the LISS is used, bone grafting is rarely necessary (0 to 1.6% in primary and 0 to 5% in secondary grafting). Also implant failure differs from the failure of plate osteosynthesis because, with the use of LISS, no screw loosening or secondary malalignment occurs. Implant failures (up to 7.4%) were recorded particularly at the time of LISS introduction in surgical practice and were attributed to the technique of implantation rather than to the implant itself. Good treatment outcomes have been reported. The average knee flexion has been 103 degrees and 107 degrees. In 72.5% of the patients, flexion has been more than 90 degrees and an extension lag of > or = 10 degrees has been found in only 7.5% of all cases. The average Neer score has ranged from 73.9 to 77.2 points. In conclusion, the LISS is a useful implant for treatment of distal femoral fractures, especially when bone quality is poor. Infection, delayed union and non-union rates are low, as shown by yet unpublished data from our clinic. Primary bone grafting, which is rarely necessary with this system, is carried out only when there is a great bone loss. Implant failure, such as screw loosening or secondary malalignment, is not seen.
Keywords: Femoral Fractures; dospělí; Internal Fixators; vnitřní fixace fraktury; lidé; Female; mužské pohlaví; radiografie; fraktury femuru; Male; interní fixátory; Radiography; Adult; Fracture Fixation, Internal; ženské pohlaví; Humans